Understanding Covid-19 Based on Clinical Insights and Recent Advancements in Therapeutic Discovery - Kurya, Abdulaziz Umar; Aliyu, Usama; Gusau, Mu’azu Abubakar (Asian Journal of Biological and Life Sciences, 2020)
An outbreak of mysterious pneumonia in December 2019 at Wuhan, China draws attention around the world. The government of Chinese and researchers employed rapid and immediate strategies to prevent and contain the outbreak. Acute Respiratory Syndrome coronavirus and the Middle East Respiratory Syndrome were found to be the causative agents of the mysterious pneumonia as a result of sequencing and etiological investigations carried out by laboratories in China. World Health Organization officially named the novel coronaviruses as COVID-19, declares it as a pandemic and potential challenge to the global health care system. This review was conducted using recent research publications from reputed journals. Since the first infected case was reported, the disease has affected more than 15 million individuals around the globe. However, there are variations on death rate base on gender, age, sex and underlining health conditions. The major symptoms of COVID-19 include: fever, headache, cough, fatigue, mild dyspnoea and sore throat. Hitherto, there is no approved drug or vaccine capable of curing COVID -19. Hitherto, physicians have been recommending the use of some FDA approved antiviral drugs such as remdesivir, chloroquine, hydroxychloroquine, glecaprevir and maraviroc which their clinical efficacy associated with the virus is still unclear. Furthermore, due to limited researches and novel approved drugs that are highly effective for COVID-19 there is a need for accelerating the on-going clinical trials to discover most effective evidence-based treatment modality to lessen the spread of this disease and prevent the burden of a future outbreak.
Keywords: 2019-nCoV; Coronaviruses and Treatment; Covid-19; SARS COV-2